Examining Turnover Intention in Manufacturing Employees: Insights from Work-Life Balance, Physical Work Environment, and Employee Engagement - Indah Astuti Dewi; Sinta Sundari Heriyanti (Lentera Ilmu Nusantara, 2026)
This study aims to analyze the influence of work-life balance, physical work environment, and employee engagement on turnover intention among employees in the Thermal Division of PT. Denso Manufacturing Indonesia. The study responds to a research gap in the turnover intention literature by examining these three factors simultaneously in a manufacturing context, particularly within an Indonesian industrial setting that remains relatively underexplored. In addition, this study contributes to the literature by providing empirical evidence on how employee-related and workplace-related factors jointly shape turnover intention in a specific organizational context. Using a quantitative approach, data were collected through a survey involving 75 randomly selected respondents and analyzed using multiple linear regression with the help of SPSS version 27. The findings show that work-life balance, physical work environment, and employee engagement significantly influence turnover intention, both partially and simultaneously. These results indicate that turnover intention is not only associated with employees’ psychological attachment to the organization, but also with the balance they experience between work and personal life as well as the conditions of the physical workplace. Based on these findings, it is recommended that the company continue to promote work-life balance, enhance the physical conditions of the workplace, and strengthen employee engagement to reduce the likelihood of employee turnover.